Humour in the management of multiple sclerosis: a scoping review - M. Šeduikienė; V. Matonis (Neurologijos seminarai)
Background. Although investigations of the use of humour in the management of people with multiple sclerosis (PwMS) are not numerous, some significant findings have created the need to go deeper into the topic. Main research question. What are some of the potential benefits of humour in the management of PwMS, given the current state of scientific knowledge? Materials and methods. A scoping review was conducted using the PRISMA-ScR methodology. Information for the literature review was collected from the PubMed and Embase databases using the keywords “humour” and “multiple sclerosis”. Overall, 10 scientific investigations were analysed, grouped, interpreted, and generalized. Results. The research revealed: humour-based stress reduction for PwMS; the relationship between executive function and humour coping in PwMS; the distinctive influence of humour on employment status among individuals with relapsing-remiting multiple sclerosis (RRMS); the relationship between humour and personal long-term prognosis in PwMS; and the differences in perception of humour in PwMS. Conclusions. Appropriate use of humour (among other factors) can significantly improve the neuropsychological status in persons with RRMS and help them staying employed. Executive function and personalized long-term prognosis for PwMS are to some extent related to humor. Group analyses revealed lower scores in RRMS patients on humoristic visual tasks compared to scores on verbal tasks, and PwMS had impaired comprehension of figurative and humorous items compared to their comprehension of the literal items of simple medical responses.